2014
DOI: 10.1016/j.aquatox.2013.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Study of genetic damage in the Japanese oyster induced by an environmentally-relevant exposure to diuron: Evidence of vertical transmission of DNA damage

Abstract: Pesticides represent a major proportion of the chemical pollutants detected in French coastal waters and hence a significant environmental risk with regards to marine organisms. Commercially-raised bivalves are particularly exposed to pollutants, among them pesticides, as shellfish farming zones are subject to considerable pressure from agricultural activities on the mainland. The aims of this study were to determine (1) the genotoxic effects of diuron exposure on oyster genitors and (2) the possible transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
73
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 65 publications
11
73
0
Order By: Relevance
“…These results were in agreement with previous studies that reduced NRR was detected in mussels and clams following exposure to contaminants such as metals, organic xenobiotics and antibiotic drugs (Lowe and Moore, 1979;Dailianis et al, 2003;Nigro et al, 2006;Rank et al, 2007;Aguirre-Martinez et al, 2013). DNA damage can lead to reproductive impairment, abnormal development and lethal mutations, which has been used as a general stress biomarker to indicate the genotoxic risk (Anguiano et al, 2007;Barranger et al, 2014;Vazquez-Boucard et al, 2014). The present study clearly demonstrated that oysters from XZ and MP were suffered from significant DNA damage.…”
Section: Discussionsupporting
confidence: 82%
“…These results were in agreement with previous studies that reduced NRR was detected in mussels and clams following exposure to contaminants such as metals, organic xenobiotics and antibiotic drugs (Lowe and Moore, 1979;Dailianis et al, 2003;Nigro et al, 2006;Rank et al, 2007;Aguirre-Martinez et al, 2013). DNA damage can lead to reproductive impairment, abnormal development and lethal mutations, which has been used as a general stress biomarker to indicate the genotoxic risk (Anguiano et al, 2007;Barranger et al, 2014;Vazquez-Boucard et al, 2014). The present study clearly demonstrated that oysters from XZ and MP were suffered from significant DNA damage.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, repression of genes implicated in immune defense system and the inhibition of enzyme activities, such as laccase-type phenoloxidase (PO) and superoxide dismutase (SOD) in the plasma, were observed in Crassostrea gigas following 2 h exposure to diuron (1 lg/L) (Luna-Acosta et al, 2012). Moreover, in the same species exposed to diuron (0.2 and 0.3 lg/L measured with POCIS), higher levels of DNA strand breaks in both hemocytes and spermatozoa occurred in genitors during the gametogenesis period (Barranger et al, 2014).…”
Section: Discussionmentioning
confidence: 87%
“…Previously, Akcha et al (2012) revealed that mature spermatozoa of the same species were highly sensitive to the genotoxicity of diuron, with an increase of DNA damage measured by the Comet assay after a 1-h-in vitro exposure from 0.05 μg L −1 . Likewise, it was demonstrated that genetic damage induced by a parental exposure to diuron in close concentrations to the ones tested here may be transmitted to progeny (Barranger et al 2014 ;Bouilly et al 2007). To our knowledge, no supplementary data exists in literature concerning the genotoxicity of diuron on spermatozoon of any other aquatic species.…”
Section: Sensitivity Of Palaemon Serratus Spermatozoa Toward Genotoximentioning
confidence: 86%